Paediatric critical procedures in the emergency department: Incidence, trends and the physician experience. (7th December 2015) - Nguyen, Lucia D; Craig, Simon
Abstract: Objectives: To analyse and provide current data surrounding paediatric critical procedures performed in three EDs of a single Victorian health network. Methods: We conducted a retrospective study of every paediatric ED attendance requiring management in a resuscitation cubicle at three Victorian hospitals in 2013. The primary outcome measure was the frequency of each paediatric critical procedure performed in the ED during the 12 month study period. Additional outcome measures included details of the proceduralist and of patient presentations. Results: Across the three EDs, there were 54 633 paediatric presentations during the study period. 5895 patients were assessed in a resuscitation cubicle and of these, only 37 presentations required one or more critical procedures (7/10 000 presentations). A total of 53 critical procedures were performed. 83% ( n = 43) of emergency physicians did not perform a single paediatric critical procedure during the study period. Endotracheal intubation was the most commonly performed critical procedure with 40 attempts (74% of procedures); however, 83% of the full‐time emergency physicians regularly exposed to paediatric presentations did not attempt or supervise a single paediatric intubation over the 12 months. 49% of patients who received a critical procedure were under 3 years of age and the most common diagnostic categories were seizure, respiratory and trauma. Conclusion: Critical procedures in children occur infrequently. Clinical exposure in the ED is therefore unreliable as the sole source of experience for critical procedures.